The Assessment of Different Positions and Attachment Adopted by Mothers During Breastfeeding - Wasaya, Sidra Allah; Hussain, Rosheen Muhammad; Shabir, Amina; Anwar, Ghuzala; Saddique, Humaira (Biological and Clinical Sciences Research Journal, 2026)
Appropriate breastfeeding positioning and attachment are essential determinants of successful lactation, adequate milk transfer, and prevention of nipple trauma. Despite global recommendations supporting exclusive breastfeeding for the first six months, technical challenges related to positioning and latch remain common among mothers. Objective: To assess the different breastfeeding positions and attachment practices adopted by mothers attending a tertiary care hospital in Lahore. Methods: A hospital-based descriptive cross-sectional study was conducted over six months (January–June 2025) in the gynecology inpatient ward, Expanded Programme on Immunization (EPI) clinic, and pediatric outpatient department of Ittefaq Hospital, Lahore. A total of 171 breastfeeding mothers were recruited using non-probability convenience sampling. Data were collected using an adopted structured questionnaire comprising demographic variables and assessment of breastfeeding positions (cradle, cross-cradle, football/rugby, and side-lying) and attachment indicators (wide mouth opening, chin-to-breast contact, alignment, switching breasts, seeking professional help, and pain/discomfort). Responses were recorded on a five-point Likert scale. Data were analyzed using SPSS, and results were summarized as frequencies and percentages. Overall practices were categorized as poor, moderate, or good based on cumulative scores. Results: Most mothers were aged 26–35 years (67.3%) and had matric/intermediate education (42.7%). Cradle hold was the most frequently practiced position (57.3% “always”), whereas football/rugby hold was rarely used (71.9% “never”). The side-lying position showed moderate utilization. Regarding attachment indicators, 68.4% always ensured a wide mouth opening before latching, 60.8% ensured nose and chin contact with the breast, and 69.6% maintained proper alignment with the baby facing the mother. However, 53.8% never sought professional help for breastfeeding positioning. Overall evaluation revealed that 45.0% of mothers demonstrated poor positioning and attachment practices, 22.8% moderate, and 32.2% good practices. Conclusion: Although commonly recommended breastfeeding positions were widely practiced, comprehensive positioning and attachment techniques were not consistently achieved. Structured antenatal and postnatal counseling, practical demonstrations, and routine assessment in clinical settings may improve breastfeeding technique and maternal comfort.